(untitled) (National Administration Journal, 2023)
There are some resilience scales originating in contexts different from Mexico, so recovering the voice and definition of the resilience concept - the ability to withstand, learn, and transcend adversity - from our national context of those who regularly use the word is convenient and necessary. The objective of this research was to psychometrically validate the ML (Montoya-Lerma) Resilience scale with 4 factors: withstand, make sense, learn, and transcend; designed and developed through natural semantic networks in the Mexican population. A total of 274 volunteer students and graduates from health and education-related bachelor’s degrees who were familiar with and regularly used the concept of resilience participated. The model of the three resilience verbs (factors withstand, learn, and transcend), socially validated and through experience, had its confrontation after statistical analysis (alpha 0.929), resulting in a fourth factor, which falls under the verb make sense, enriching the analysis of the resilient process and consolidating this instrument as a new benchmark for measuring this construct.